Probability, random variables, and random process - Hsu, Hwei P. (New York, NY : McGraw-Hill, 2011)
This ideal review for electrical engineering college students covers probability, random variable, functions of random variables, and more.
Includes index. Rev. ed. of: Schaum's outline of theory and problems of probability, random variables, and random processes / Hwei Hsu. c1997.
Keywords: Probabilities -- Outlines, syllabi, etc; Random variables -- Outlines, syllabi, etc; Stochastic processes -- Outlines, syllabi, etc